Can Self-Efficacy and Task Values Buffer Perceived Costs? Exploring Introductory- and Upper-Level Physics Courses. Issue 4 (13th July 2022) - Kim, Yeo-eun; Yu, Shirley L.; Koenka, Alison C.; Lee, Hyewon; Heckler, Andrew F.
Abstract: Students' cost perceptions have been associated with lower retention and academic performance in science, technology, engineering, and mathematics (STEM). Guided by expectancy-value theory, we examined whether relations between perceived costs and physics outcomes (i.e., engagement and achievement) varied as a function of self-efficacy or task values among undergraduate physics students ( N = 1, 124). We also examined whether the interactive relations were further moderated by course level in the curricular sequence. Overall, findings from moderated moderation analyses indicated that perceived costs were negatively related to different components of engagement (i.e., effort, persistence, procrastination, and choice) and achievement (i.e., physics course grades). However, the magnitude of relations often depended on levels of self-efficacy or task value. Some of the interactive relations between these variables also differed between introductory- and upper-level physics courses. Taken together, results indicated that higher self-efficacy or task values do not compensate for the negative effects of perceiving high cost on engagement. Moreover, cost perceptions were in some cases more negatively related to engagement when students reported higher self-efficacy or task values. Finally, mitigating cost perceptions may be particularly important in introductory undergraduate physics courses. Implications and directions for future research are discussed.